2018
DOI: 10.1002/smll.201802050
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Powered Multifunctional Transient Bioelectronics

Abstract: Controllable degradation and excellent biocompatibility during/after a lifetime endow emerging transient electronics with special superiority in implantable biomedical applications. Currently, most of these devices need external power sources, limiting their real-world utilizations. Optimizing existing bioresorbable electronic devices requires natural-material-based construction and, more importantly, diverse or even all-in-one multifunctionalization. Herein, silk-based implantable, biodegradable, and multifun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 46 publications
0
60
0
Order By: Relevance
“…Typically, the same PET/ITO substrates are selected as the reference friction layer of TENG in all pairwise combinations. These results indicate the intriguing output performance of RSSP‐TENG that differentiate itself from other biomaterials and merit a wide range of self‐powered applications …”
Section: Comparison Of Various Large‐scale Biomaterial‐based Tengs Asmentioning
confidence: 89%
See 2 more Smart Citations
“…Typically, the same PET/ITO substrates are selected as the reference friction layer of TENG in all pairwise combinations. These results indicate the intriguing output performance of RSSP‐TENG that differentiate itself from other biomaterials and merit a wide range of self‐powered applications …”
Section: Comparison Of Various Large‐scale Biomaterial‐based Tengs Asmentioning
confidence: 89%
“…However, challenges still remain for large‐scale manufacturing of TENGs with high performances [so to be competitive to their conventional counterparts using organic and inorganic materials such as gold and poly(dimethylsiloxane) (PDMS)] towards real‐world applications . For example, the performance of TENGs are mainly determined and limited by the triboelectric pair materials, such as many commercially available organic materials [e.g., silk, poly(tetrafluoroethylene), poly(ethylene terephthalate) (PET), polyimide (PI), PDMS, fluorinated ethylene propylene (FEP), poly(lactic acid) (PLA), and poly(methyl methacrylate)] and inorganic ones [e.g., indium tin oxide (ITO), Al, Cu, Au, Ti, TiO 2 , Si, and SiO 2 ] . Nevertheless, efforts are needed on exploring materials via genetic engineering to design and further modulate the material properties from the gene level to increase the triboelectric effects, and importantly, to add extra (biological, in particular) functionalities on demand.…”
Section: Comparison Of Various Large‐scale Biomaterial‐based Tengs Asmentioning
confidence: 99%
See 1 more Smart Citation
“…Another highly promising material which is biocompatible, provides high mechanical strength and has a unique structure is spider silk [94][95][96]. Zhang et al [97] have demonstrated the potential of a TENG based on recombinant spider silk.…”
Section: Natural Biodegradable Materialsmentioning
confidence: 99%
“…[14,17,20,27] The AgNWs were purchased from Aladdin with length of 200 µm. [14,17,20,27] The AgNWs were purchased from Aladdin with length of 200 µm.…”
Section: Methodsmentioning
confidence: 99%